On the Finite Groups that all Their Semi-Cayley Graphs are Quasi-Abelian - Majid Arezoomand (Mathematics Interdisciplinary Research, 2018)
In this paper, we prove that every semi-Cayley graph over a group G is quasi-abelian if and only if G is abelian.